PENERAPAN PERMAINAN INFO BERANTAI DAN KATA MENGALIR PADA PEMBELAJARAN BERBICARA BAHASA JERMAN KELAS X IPA 2 SEMESTER II SMAN 12 SURABAYA - Efi Sutrisnaningsih (Universitas Negeri Surabaya, 2022)
This research focused on using of both game techniques: Information Chain and Flowing Words in student’s speaking skills. This Information Chain and Flowing Word Learning Technique were applied in German class, so that students have the courage to speak German. This study examines two research problems: (1) How are the information chain game technique and word flow used for the speaking skill of students of class X IPA 2 SMA Negeri 12 Surabaya? (2) How are the results of learning German speaking skills through the usage of chained information learning techniques and words flowing in German at SMA Negeri 12 Surabaya. This study used a chain of info and word flow to train student’s speaking skill. This research is a descriptive research with a qualitative approach. Based on this research, it can be concluded that these game techniques such as information chain and word flow can be used in the teaching process of speaking skills. Because the student learning outcomes are indicated by an increased score oft class average and from the results of the Pre-Test and Post-Test the average of student learning outcomes in speaking skills increase. Keywords: Info chain game technique, word flow technique, speaking skill.